Dynamics of linear morphometrical parameters of ventral surface of hococerebral part of cattle skull depending on age and sex - Абузнайд Карем, Р. С. (Scientific Progress & Innovations, 2015)
Linear morphometric parameters of the ventral surface of the hoco-cerebral part of the skull of both males and females of cattle trustworthy increased from birth to 10-year age. Two periods were registered in the dynamics of morphometrical parameters of the ventral surface of the hoco-cerebral part of the skull: preboundary and post-boundary ones. The identified age regularities of metric parameters of the ventral surface of the hoco-cerebral part of the skull in the cattle have been used as a basis of the method to determine animal age and sex by informative morphometrical parameters.